Test of Total Solids and Melting Rate of Coconut Milk-Based Ice Cream Combined with Cashew Milk - Iwank Afifa, Salsa; Kurnia, Pramudya (Newinera Publisher, 2024)
Ice cream is one of the most popular foods, favored by people of all ages, from children to adults. Cow's milk is generally the primary ingredient for making ice cream. However, due to limited production and relatively high prices of cow's milk, alternatives such as coconut milk and cashew milk combinations are being explored. The quality of ice cream is influenced by total solids and melting rate. This study aims to determine the total solids and melting rate of coconut milk-based ice cream with the addition of cashew milk. This research is an experimental study using a Completely Randomized Design (CRD) with three treatments, varying the composition of coconut milk to cashew milk in ice cream production: 60%:40%, 50%:50%, and 40%:60%. The research procedure consisted of three stages:(1)Ice cream production;(2)Testing total solids in ice cream products;(3)Testing the melting rate of ice cream products Data were processed through editing, coding, tabulating, and entry. Statistical analysis was performed using a one-way ANOVA test. Results showed a significant difference in total solids among the treatments with varying ratios of coconut milk to cashew milk. Ice cream A had the highest total solids at 23.412%. However, the total solids values did not meet the quality requirements of the Indonesian National Standard (SNI). Regarding melting rate, no significant difference was found among the treatments. Ice cream A exhibited the highest melting resistance with an average value of 0.865. The melting rate values met the SNI quality requirements, with an average melting time of 45 minutes.